TIME MANAGEMENT AND EDUCATION EFFICIENCY: TIME MANAGEMENT COMPETENCE - Bekniyazov, Bayram Saparbaevich (SCIENCE and SOCIETY, 2026)
This article, based on scientific literature, comprehensively analyzes the scientific and theoretical foundations for developing time management skills in the management activities of general education school principals. The article covers the development of time management skills among heads of educational institutions.